THE INFLUENCE OF MADRASAH PRINCIPAL'S LEADERSHIP STYLE ON TEACHER WORK MOTIVATION AND PERFORMANCE: LITERATURE REVIEW - Enika Sari; Sunhaji (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study aims to analyze the influence of madrasah principals’ leadership styles on teachers’ motivation and performance. The method used is a descriptive qualitative approach through a literature study. The discussion covers four leadership styles: authoritarian, charismatic, laissez-faire, and democratic. The findings indicate that the authoritarian style tends to reduce teachers’ motivation and long-term performance, while charismatic leadership can enhance both through inspiration and emotional support. The laissez-faire style is effective for independent teachers but may weaken motivation for those who require guidance. Meanwhile, the democratic style provides the most positive impact as it encourages participation, creativity, and a sense of ownership in the workplace. Therefore, an appropriate leadership style plays an essential role in improving teachers’ motivation and performance in madrasah settings. Keywords: Leadership Style, Work Motivation, Teacher Performance Abstrak Penelitian ini bertujuan menganalisis pengaruh gaya kepemimpinan kepala madrasah terhadap motivasi dan kinerja guru. Metode yang digunakan adalah penelitian kualitatif deskriptif dengan studi literatur. Pembahasan mencakup empat gaya kepemimpinan: otoriter, karismatik, laissez-faire, dan demokratis. Hasil kajian menunjukkan bahwa gaya otoriter cenderung menurunkan motivasi dan kinerja jangka panjang, sedangkan kepemimpinan karismatik mampu meningkatkan keduanya melalui inspirasi dan dukungan emosional. Gaya laissez-faire efektif bagi guru yang mandiri, tetapi dapat melemahkan motivasi bagi guru yang membutuhkan arahan. Adapun gaya demokratis memberikan dampak paling positif karena mendorong partisipasi, kreativitas, dan rasa memiliki dalam bekerja. Dengan demikian, gaya kepemimpinan yang tepat berperan penting dalam meningkatkan motivasi serta kinerja guru di lingkungan madrasah. Kata Kunci: Gaya Kepemimpinan, Motivasi Kerja, Kinerja Guru